Source usage and news credibility in two Malaysian crime cases - Wilson, Sharon (Universiti Kebangsaan Malaysia, 2010)
The use of credible or trustworthy sources has been controversial and editors have also constantly been distressed over the use of sources, fearing that they were depending on them too heavily and damaging the press credibility. Nevertheless, news without sources are not news. Before journalists publish stories, editors and journalists strongly favour checking the story with sources to ensure accuracy. However, because of deadline pressure, journalists are prevented from waiting for sources to review the whole story and use anonymous sources instead. Here is when conflict arises as some critique anonymous sources as unreliable and effecting news credibility and yet newsmen consider them essential, vital especially in breaking news items. A research was conducted to uncover the use and roles of sources in two particular crime cases in Malaysia. Besides textual analysis, intensive interviews were employed to explore the impact that sources bring towards news credibility especially where crime news is concerned. At the same time there researcher puts forth questions fro the reader to ponder such as what determines news source credibility? Are they that unreliable that they should never be used? Based on the preliminary findings and secondary findings from a research done previously, this article discusses the general assumptions of using sources, the types of sources used and the impact of using anonymous sources especially in crime reporting in the Malaysian news context